2001
DOI: 10.1002/eat.1017
|View full text |Cite
|
Sign up to set email alerts
|

Males with anorexia nervosa: A controlled study of eating disorders in first‐degree relatives

Abstract: Although anorexia nervosa in males is exceedingly rare, there is a pattern of familial aggregation that is highly similar to that observed in recent family studies of affected females. On the basis of these findings, there is no evidence that familial-genetic factors distinguish the occurrence of anorexia nervosa in the two sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 17 publications
6
34
0
3
Order By: Relevance
“…In general, these findings concur with the relatively few clinical studies of gender influences in anorexia nervosa that have suggested minimal differences between males and females in symptom phenomenology, 6-8 but a possibly greater intensity of specific weight concerns among females. 5 Combined with our earlier report of strong familial transmission of anorexia nervosa in male patients, 16 the present findings support the descriptive, nosological validity of anorexia nervosa across genders.…”
Section: Resultssupporting
confidence: 90%
“…In general, these findings concur with the relatively few clinical studies of gender influences in anorexia nervosa that have suggested minimal differences between males and females in symptom phenomenology, 6-8 but a possibly greater intensity of specific weight concerns among females. 5 Combined with our earlier report of strong familial transmission of anorexia nervosa in male patients, 16 the present findings support the descriptive, nosological validity of anorexia nervosa across genders.…”
Section: Resultssupporting
confidence: 90%
“…49 Interestingly, this pattern of familial aggregation between muscle dysmorphia and anorexia nervosa is remarkably similar to the familial transmission of anorexia nervosa between first-degree relatives. 50 …”
Section: 26mentioning
confidence: 99%
“…While most characteristics of men and women with EDs are similar, men have been reported to have higher levels of Axis I (Woodside et al, 2001), and Axis II (StriegelMoore, Garvin, Dohm, & Rosenheck, 1999) comorbidity, more frequent homosexuality (Bramon-Bosch, Troop, & Treasure, 2000), more premorbid overweight or obesity (Ferná ndez-Aranda et al, 2004) and a later onset (Braun, Sunday, Huang, & Halmi, 1999;Grabhorn, Kopp, Gitzinger, von Wietersheim, & Kaufhold, 2003). Other studies have failed to find gender differences in personality traits (Ferná ndezAranda et al, 2004) or familial-genetic or individual risk factors (Strober, Freeman, Lampert, Diamond, & Kaye, 2001).…”
Section: Introductionmentioning
confidence: 98%